(untitled) (International Journal of Contemporary Security Studies, 2022)
The recent pandemic COVID-19 has become inevitably a comprehensive crisis that challenges, like a war, the very state and society functioning. The situation of global instability and fear puts a logical question: who is responsible for vital things – security and safety of citizens? The traditional answer is the national state, as it constitutes its natural function. However, in last decades this postulate has only caused controversy and extended debates among academics and practitioners who support an idea of reducing the state role and loosing some of its functions in globalizing world in favour of civil society as well as trans- and supranational institutions. The principle purpose of this article is to reveal objective grounds for re-etatization of public life and renationalization of international relations during the period of countering pandemic and at the post-pandemic stage. The authors are also endeavoring to join discussions concerning setting the limits of state powers expanding in a crisis, as well as the validity of the absolutism in etatistic, authoritarian and paternalistic practices as universal tools of crisis management. The problems under discussion are considered through the milieu of ensuring and preservation of human rights, freedoms and security of human communities.